Impacto econômico do agronegócio no município mato-grossense de Sorriso (1989 a 2012) - Moraes, Arthur Ricardo Pinheiro de Souza (2017)
This dissertation highlights the expressive growth of the economy of Mato Grosso, mostly, justified by the agribusiness strength. Allied to the extensive area destined to the production, the State acquired a prominent role in front of the other Brazilian states, as the expressive city of Sorriso. Since its inception on May 13, 1986, Sorriso has begun to show signs of a strong trend towards agribusiness activity, especially in soybeans. Becoming known as the "agribusiness world capital", Sorriso results from a colonization project that took place in the 1970s. It is a city formed by Paraná and Santa Catarina, and many of the "first inhabitants" who participated in its construction, remain unknown. This research identifies these first inhabitants, increasing the impacts of agribusiness on urban economic development, the value invested by the municipality, with emphasis on health and education, the state of commerce, agribusiness and infrastructure, as well as a global balance of incomes and expenses, from 1989 to 2012, through interviews, surveys, documents, reports, newspapers, magazines and photos.